Fibril formation pH controls intrafibrillar collagen biomineralization in vitro and in vivo. (January 2015) - Marelli, Benedetto; Ghezzi, Chiara E.; Zhang, Yu Ling; Rouiller, Isabelle; Barralet, Jake E.; Nazhat, Showan N.
Abstract: We demonstrate that intrafibrillar, homogenous collagen biomineralization can be achieved by controlling self-assembly under mildly alkaline conditions. Using dense collagen (DC) gels as an osteoid model, we modulated their fibrillogenesis environment to evaluate the effects of fibrillogenesis pH on the protein charge distribution and ultimately on biomineralization. Cationic and anionic dye staining and electron cryomicroscopy analyses established that fibrillogenesis under mildly alkaline conditions promotes the formation of electronegative charges within the protein (anionic DC gels). These charges are stable upon titration of the gel pH to physiological values. Subsequent exposure of anionic DC gels to simulated body fluid induced the intrafibrillar biomineralization of the gels, promoting a rapid, extensive formation of carbonated hydroxyapatite, and strongly impacting gel mechanical properties. The generality and significance of this approach has been addressed by implanting freshly made anionic DC gels in vivo, in a rat subcutaneous model. Subcutaneous implants showed an extensive, homogenous biomineralization as early as at day 7, indicating that anionic collagen gels rapidly self-mineralize upon contact with body fluids in a non-osseous implantation site. The control of collagen fibrillogenesis pH provides not only new interpretations to what has been called the collagen mineralization enigma by demonstrating that neat collagen can intrafibrilarly self-mineralize, but it will also set a new starting point for the use of DC gels in bone regenerative medicine, in addition as potential applications as mineralized tissue model or as slow-release delivery carriers.